IN VITRO VARIATION OF GLYCOGEN CONTENT IN NODULAR WORM AND WHIP WORM OF SHEEP - SHARMA, SAVITA; KUMAR, D.; SHARMA, MONA; SHARMA, MONA; SHARMA, S.K.; KUMAR, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2004)
In vitro variation of glycogen content under aerobic conditions was measured on fresh weight basis in Oesophagostomum columbianum (nodular worm) and Trichuris ovis (whip worm) of sheep. Male and female parasites were separated and starved for varying period of time upto 24 hrs in glucose free physiological saline. The difference between females and males of both the species with respect to glycogen content and its rate of change with time are discussed.